2007
DOI: 10.2139/ssrn.965785
|View full text |Cite
|
Sign up to set email alerts
|

Bad Luck or Bad Management? Emerging Banking Market Experience

Abstract: The Working Paper Series of the Czech National Bank (CNB) is intended to disseminate the results of the CNB's research projects as well as the other research activities of both the staff of the CNB and collaborating outside contributor, including invited speakers. The Series aims to present original research contributions relevant to central banks. It is refereed internationally. The referee process is managed by the CNB Research Department. The working papers are circulated to stimulate discussion. The views … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 17 publications
4
29
0
4
Order By: Relevance
“…To address these issues, we use the system GMM estimators developed for dynamic panel models by Arellano and Bover (1995) and Blundell and Bond (1998). Podpiera and Weill (2008) and Fiordelisi et al (2011) also use similar frameworks.…”
Section: The Granger-causality Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these issues, we use the system GMM estimators developed for dynamic panel models by Arellano and Bover (1995) and Blundell and Bond (1998). Podpiera and Weill (2008) and Fiordelisi et al (2011) also use similar frameworks.…”
Section: The Granger-causality Frameworkmentioning
confidence: 99%
“…Our study is limited to a single country, as in these studies, because we require very detailed data (e.g., Podpiera and Weill 2008;Pruteanu-Podpiera, Weill and Schobert 2008, for Czech banks;Casu and Girardone 2009;and Fiordelisi et al 2011, for European banks). Measuring liquidity creation requires this kind of data because balance-sheet items need to be classified to compute liquidity creation measures.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them show that because of banks can choose their level of operating costs, monitoring cots and capitalization to manage their level of risk exposure (e.g. adequate proportion of riskier loans), the consequences of a bad management or higher risk-taking, by skimping or moral hazard incentives, would lead to both inefficiency and higher bad loans (see Williams, 2004;Altunbas et al, 2007;Lepetit et al, 2008;Podpiera and Weill, 2008;Tabak et al, 2011).In general, they find a negative relationship between NPLs and cost efficiency and concur that banking supervisors should focus on enhancing bank cost efficiency and bank capital in order to reduce the probability of bank failures and to support financial stability objectives. However, little is known about how differences in risk exposure affect the efficiency of banks with different characteristics.…”
Section: Risk-taking and Bank Efficiencymentioning
confidence: 99%
“…The seminal work of Berger and DeYoung (1997) showed that banks with lower efficiency tend to exhibit higher ratio of bad loans and in turn those banks are more prone to default than banks with higher efficiency and lower share of bad loans. Thus, bank efficiency indicators have been used as a potential measures of bank failures (Podpiera and Weill, 2008). Likewise, the modern banking theory highlights that risk-taking is an inherent element of the banking production which should be properly modeled into the efficiency measurement (Hughes et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…External factors have been seen as macro-economic variables such as currencies, real interest rates or unemployment rates or the indexes (Podpiera and Weill, 2008), whereas internal factors are seen as bank specific factor like size, profitability or cost efficiency measurements (Berge and Boye, 2007) There are also other interesting researches which are concentrated on the internal process to determine the non-performing loan factors. Li et all (2007) in their research scrutinized the incentive contracts and managerial efforts.…”
Section: Introductionmentioning
confidence: 99%